1995
DOI: 10.1103/physreva.52.1936
|View full text |Cite
|
Sign up to set email alerts
|

Determination of radiative lifetimes of neutral bismuth by time-resolved uv-vuv laser spectroscopy

Abstract: Time-resolved laser spectroscopy was used to measure natural radiative lifetimes of ten excited states of neutral bismuth. Four levels of the 6p ns P&/& sequence (n =7,8,9, 10) and the 6p 7s P3/2 5/2 and 6p nd D3/2. 5/2 (n =6,7) levels were investigated. The results are compared with previous data when possible. Revised absolute transition probabilities for 26 lines are given. Several levels required vacuum-ultraviolet (vuv) excitation, which was achieved by stimulated anti-Stokes Raman shifting of frequency-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…A similar situation has been met in Bi I where it has been observed that the measurements from Ref. [21], when compared with accurate time-resolved laser spectroscopy measurements [22], show, for some levels, large discrepancies which can reach a factor of 3! As a consequence, the delayed-coincidence results for Bi II need also to be checked by new accurate laser measurements.…”
Section: The Hfr Transition Probabilitiessupporting
confidence: 63%
See 1 more Smart Citation
“…A similar situation has been met in Bi I where it has been observed that the measurements from Ref. [21], when compared with accurate time-resolved laser spectroscopy measurements [22], show, for some levels, large discrepancies which can reach a factor of 3! As a consequence, the delayed-coincidence results for Bi II need also to be checked by new accurate laser measurements.…”
Section: The Hfr Transition Probabilitiessupporting
confidence: 63%
“…Radiative lifetimes of 18 atomic and 13 ionic levels of bismuth have been measured [21] using a multichannel delayed coincidence method with crossed beam (atoms and electrons). However, a recent comparison of the latter results with accurate time-resolved laser spectroscopy measurements [22] in neutral bismuth has shown, for some levels, large discrepancies.…”
Section: Introductionmentioning
confidence: 97%
“…Data on atomic properties are relevant not only for spectroscopy; these values are also of interest in a variety of other fields in physics and technology. Calculations of oscillator strength for different transitions in Thallium, Bismuth and Germanium has been the subject of numerous theoretical studies [4][5][6][7][8].…”
Section: Procedure Results and Discussionmentioning
confidence: 99%
“…To provide level energy for our calculation we have used the Tables of Moore [10]. 'Biemont et al (1999) ' Caiyan et al (1995) ' Alonso-Medma(1996a) ' Ahnso-Medina(1997) Also in this work we present experimental values for several lines corresponding to different transitions of Tl I, Tl II, Ge I, Ge II, Bi I and Bi II. Relative values have been obtained from measures of emission hue intensities in hollow cathode lamp discharges operating with a typically current of 10 mA.…”
Section: Procedure Results and Discussionmentioning
confidence: 99%
“…Transitions belonging to the Bi I and Bi II systems were identified during this study. They are listed in Table 1 (see Figure S1 for the visualization of transitions in the corresponding Grotrian diagrams) [ 26 , 27 ]. The last three columns contained data evaluated for the present study from the experimental spectra.…”
Section: Methodsmentioning
confidence: 99%